Męczeństwo formą samobójstwa? - Marcin Cholewa (Polonia Sacra)
The article focuses on key elements of martyrdom (conscious and voluntary acceptance of death, dying for the faith, virtues pertaining to God, bearing witness to truth and love, patient endurance until death, externalised defending the truth of faith, a persecutor as opposed to the martyr, no pursuit of martyrdom, the pursuit of martyrdom not for its glory) and altruistic suicide (conscious and voluntary acceptance of death, death for the sake of others, society, bearing witness to the values, God, honour, friendship, freedom, desire for death without reward, death as a personal act, not harming innocent people, exceptions are acts of terrorism and suicide acts during wars). It seems that martyrdom and altruistic suicide are, using the language of mathematics, two different sets having a common part. Because of that there arises a considerable difficulty while classifying borderline situations. An auxiliary, though an insufficient criterion for martyrdom, appears to be external efficacy. The other element is the acceptance of death in the case of martyrdom, rather than striving for it. The sense of faith of people gathering at the grave of a martyr may be an essential element.